Conspiracy of Silence in Head and Neck Cancer Diagnosis: A Scoping Review - Cristina Saldivia-Siracusa; Erison Santana Dos Santos; Wilfredo Alejandro González-Arriagada; Ana Carolina Prado-Ribeiro; Thaís Bianca Brandão; Adepitan Owosho; Marcio Ajudarte Lopes; Joel B. Epstein; Alan Roger Santos-Silva (MDPI AG, 2024)
Cancer disclosure represents a complex healthcare dynamic. Physicians or caregivers may be prompted to withhold diagnosis information from patients. This study aims to comprehensively map and synthesize available evidence about diagnosis nondisclosure regarding head and neck cancer (HNC) patients. Following the Joanna Briggs Institute guidelines, a scoping review was conducted across major databases without period restriction, yielding 9238 publications. After screening and selection, a descriptive synthesis was conducted. Sixteen studies were included, primarily conducted in academic settings (75%) from Europe and Asia, with a total population of 662 patients predominantly diagnosed with brain, oral, pharyngeal, or laryngeal tumors. Remarkably, 22.51% of patients were unaware of their diagnosis. Although physicians were the main source of diagnostic information (35%), they reported to often use vague terms to convey malignancy. Additionally, 13.29% of patients were aware of their diagnosis from sources other than doctors or caregivers. Caregivers (55%) supported diagnosis concealment, and physicians tended to respect family wishes. A high diagnosis-to-death interval, education, and age significantly influenced diagnosis disclosure. HNC patients expressed a desire for personalized open communication. Multiple factors influenced the decision on diagnosis disclosure. Current evidence on this topic varies significantly, and there is limited research on the consequences of nondisclosure. These findings reflect the underestimation of the patients' outlook in the diagnosis process and highlight the need for further research, aiming to establish open communication and patient autonomy during the oncological journey.